Aplikasi Edukatif Pengenalan Huruf Dan Angka Untuk Anak Usia Dini Berbasis Android - Bramastya, Indrawan Dwi, Dedi Gunawan S.T., M.Sc (2016)
Early Childhood Education (ECD) levels, is one of the forms of education that focuses on the foundation to wards growth and physical development of the motor coordination and intelligence, which includes the intellectual, creativity, emotional intelligence, spiritual intelligence, socio-emotional condition (attitudes, behavior, and religion) as well as language and communication. Learners priority for children age 5 to 7 years old. The 2013 curriculum (K-13) is considered the most ideal applied.The methodology used in this research is software waterfall development method which includes several stages of the needs analysis, design, manufacture, testing, implementation. This application is built using Android Studio software with the Java programming language and XML . The results of this study is an application that can be run on the Android operating system 4.0.3 ( IceCreamSandwich )upwards.This android based educational applications built as media literacy and numeracy, whether it's reading, writing, and counting by using two languages, Arabic and Indonesian. The results of application testing that has been done is very nice , usefull application and good response from user.